2000
DOI: 10.1159/000026667
|View full text |Cite
|
Sign up to set email alerts
|

Potential Human Neurotoxicity of MDMA (‘Ecstasy’): Subjective Self-Reports, Evidence from an Italian Drug Addiction Centre and Clinical Case Studies

Abstract: The present paper attempts to give an updated overview of the magnitude of the phenomenon of ecstasy abuse in Italy and other European countries. It gives an account of some clinical case studies and of a larger-scale report on polydrug (including MDMA) consumers attending our Public Health Addiction Treatment Unit in recent years, with a view to clarifying the characteristics and psychopathological consequences (mainly depression, psychotic disorders, cognitive disturbances, bulimic episodes, impulse control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
1
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 31 publications
9
80
1
4
Order By: Relevance
“…One dose of 10 mg/kg MDMA (i.p., 3 h), identical to that used under our experimental conditions, was found to increase 5-HT turnover in mouse brain (Steele et al, 1989). Few studies indicate that MDMA exerts an effect on food consumption in humans (anorectic or bulimic effects) (Shulgin, 1986;Rochester and Kirchner, 1999;Schifano, 2000), as would be expected from its 'substrate-type 5-HT releaser' activity. Furthermore, only one study reports its hypophagic effect in rats (Frith et al, 1987).…”
Section: Discussionsupporting
confidence: 62%
“…One dose of 10 mg/kg MDMA (i.p., 3 h), identical to that used under our experimental conditions, was found to increase 5-HT turnover in mouse brain (Steele et al, 1989). Few studies indicate that MDMA exerts an effect on food consumption in humans (anorectic or bulimic effects) (Shulgin, 1986;Rochester and Kirchner, 1999;Schifano, 2000), as would be expected from its 'substrate-type 5-HT releaser' activity. Furthermore, only one study reports its hypophagic effect in rats (Frith et al, 1987).…”
Section: Discussionsupporting
confidence: 62%
“…Fox et al (2001) found that significantly more Ecstasy users took amphetamine, cocaine, or LSD, in comparison with cannabis-user controls. Other studies have similarly noted that multiple psychoactive drug use is a typical characteristic of Ecstasy users Morgan, 1999;Parrott et al, 2000Parrott et al, , 2001Pedersen & Skrondal, 1999;Schifano, 2000;Topp et al, 1999). These findings are consistent with the notion of thresholds, that drug escalation follows a characteristic progression, from legal drugs, to cannabis, then other illicit Table 3 Normal Ecstasy dose per occasion and maximum number of Ecstasy tablets taken in 1 week, reported by novice, moderate, and heavy Ecstasy/MDMA users (1 -9, 10 -99, and + 100 lifetime occasions; N = 109, 136, and 37, respectively) drugs.…”
Section: Discussionmentioning
confidence: 89%
“…Around 5% of schoolchildren in the Netherlands have used it, as have 13% of British university students (Spruit, 2001;Webb, Ashton, Kelly, & Kamali, 1996). Its use is strongly associated with the dance club and rave scene, with 59% of Italian disco clubbers and 81% of Dutch ravers having experienced it, and 64% of the Dutch sample stating that they had taken Ecstasy the previous night (Schifano, 2000;Spruit, 2001). In the United States, its availability has also increased dramatically in recent years, so that it is now one of the most frequently used recreational drugs (Chang, 2001;Schensul, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies reported increased levels of depression (Sumnall and Cole, 2005), impulsivity (Morgan, 1998;Parrott et al, 2000;Tuchtenhagen et al, 2000;Daumann et al, 2001Daumann et al, , 2004bBond et al, 2004;Butler and Montgomery, 2004), and sensation/novelty seeking (Gerra et al, 1998;Tuchtenhagen et al, 2000;Schifano, 2000;Dughiero et al, 2001) in ecstasy users, although it is unclear whether these associations reflect a causal relationship, that is whether ecstasy use causes changes in mood, impulsivity, and sensation seeking or whether depression, impulsivity, and sensation seeking increase the probability of (heavy) ecstasy use (see also De Win et al, 2006).…”
Section: Introductionmentioning
confidence: 99%